Parallax Barrier for Weakening Vernier Fringe in Naked-Eye LED 3D Display - Hong-Ran Zeng; Wu-Xiang Zhao (International Journal of Optics)
In naked-eye LED 3D display, vernier fringe is apparent for a conventional parallax barrier. This paper presents an intended misplaced parallax barrier with discrepant width of Light Translucent Slits (LTSs) to weaken vernier fringe. Because of the wild Black Matrix (BM) of LED display, which causes apparent vernier fringe, we enlarge the width of the LTS and move the slits properly in their periods. This structure increases the periodic difference between the parallax barrier and pixel of the LED display, which can increase the brightness of the diazone of vernier fringe and make it to appear more sparsely. In this way, vernier fringe produced by those two periods is weakened at the condition that no obvious crosstalk of stereoimages is increased. The performances of simulation and experimental display prototype show that the diazone of vernier fringe is faded and obviously sparser in the naked-eye LED 3D display. As a result, vernier fringe of this display is significantly decreased and not visible for viewing.